Self-coping mechanism of single mothers to achieve financial security in life - Ahmad, Siti Yuliandi; Sabri, Mohamad Fazli; Abd Rahim, Husniyah; Osman, Syuhaily (Zes Rokman Resources, 2018)
Financial security from the consumer perspective is linked to the level of savings, the ability of individuals to meet an emergency, the adequacy of financial resources in retirement and the availability of income. Stress occurs when the individual is faced with a higher demand that exceeds the individual financial resources. The stressor event such as loss of spouse, divorce, disability of spouse also might lead to the financial strains. Thus, from health and psychological aspect of self-coping mechanism, it is how the individual’s effort to manage financial strains. This study focused on the self-coping mechanism of single mothers and their contingency strategies to achieve financial security. The relationship between selfcoping mechanisms and financial security provide better understanding on cognitive, financial and behavior of single mothers. The significant positive relationship between self-coping mechanisms and financial security indicated that selfcoping mechanisms are compensatory coping in which individuals adopt a problem-focused approach in facing stressor events. The academic research, especially consumer science researchers and non-profit organization could incorporate these elements of social support to encourage positive self-coping mechanism among single mother in order to achieve better financial security.